Plasma cholesterol-lowering activity of dietary dihydrocholesterol in hypercholesterolemia hamsters. Issue 1 (September 2015) - Wang, Xiaobo; Guan, Lei; Zhao, Youyou; Lei, Lin; Liu, Yuwei; Ma, Ka Ying; Wang, Lijun; Man, Sun Wa; Wang, Junkuan; Huang, Yu; Chen, Zhen-Yu
Abstract: Objective: Cholesterol analogs have been used to treat hypercholesterolemia. The present study was to examine the effect of dihydrocholesterol (DC) on plasma total cholesterol (TC) compared with that of β-sitosterol (SI) in hamsters fed a high cholesterol diet. Methods and Results: Forty-five male hamsters were randomly divided into 6 groups, fed either a non-cholesterol diet (NCD) or one of five high-cholesterol diets without addition of DC and SI (HCD) or with addition of 0.2% DC (DA), 0.3% DC (DB), 0.2% SI (SA), and 0.3% SI (SB), respectively, for 6 weeks. Results showed that DC added into diet at a dose of 0.2% could reduce plasma TC by 21%, comparable to that of SI (19%). At a higher dose of 0.3%, DC reduced plasma TC by 15%, less effective than SI (32%). Both DC and SI could increase the excretion of fecal sterols, however, DC was more effective in increasing the excretion of neutral sterols but it was less effective in increasing the excretion of acidic sterols compared with SI. Results on the incorporation of sterols in micellar solutions clearly demonstrated both DC and SI could displace the cholesterol from micelles with the former being more effective than the latter. Conclusion: DC was equally effective in reducing plasma cholesterol as SI at a low dose. Plasma TC-lowering activity of DC was mediated by inhibiting the cholesterol absorption and increasing the fecal sterol excretion. Graphical abstract: Highlights: This work demonstrated that dietary supplement of dihydrocholesterol (DC) could significantly lower plasma cholesterol. The cholesterol lowering activity of DC was comparable to that of β-sitosterol. The cholesterol lowering activity of DC was mediated by increasing the excretion of both neutral and acidic sterols.